Vibration Parameters for Impact Detection of Composite Panel: A Neural Network Based Approach - Arena, Maurizio; Viscardi, Massimo (Journal of composites science, 2021)
The need for reliable methodologies for structural monitoring is certainly a current line of research in many engineering sectors. The detection of the impact on composite materials is in fact a recent subject of study, aimed at safeguarding the mechanical integrity and improving the useful life of structural components. In such a context, the work deals with evaluation of the use of neural algorithms for localizing the position of the impacts on composite structures. Starting from FE (finite element) simulations, representative of the dynamic response of a CFRP (Carbon Fiber Reinforced Polymer) panel as a benchmark, the approach has been finally validated experimentally by modal parameters identification.